2017
DOI: 10.7554/elife.27014
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of life span by the gut microbiota in the short-lived African turquoise killifish

Abstract: Gut bacteria occupy the interface between the organism and the external environment, contributing to homeostasis and disease. Yet, the causal role of the gut microbiota during host aging is largely unexplored. Here, using the African turquoise killifish (Nothobranchius furzeri), a naturally short-lived vertebrate, we show that the gut microbiota plays a key role in modulating vertebrate life span. Recolonizing the gut of middle-age individuals with bacteria from young donors resulted in life span extension and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
294
3
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 344 publications
(310 citation statements)
references
References 79 publications
(106 reference statements)
11
294
3
2
Order By: Relevance
“…( 2016), Martino, Ma and Leulier ( 2017), Smith et al. ( 2017), Tropini, Earle, Huang and Sonnenburg ( 2017); excretory system: King and Goldstein (1985), Buechner (2002), Gautam, Verma and Tapadia ( 2017); sleep and circadian system: Raizen et al. ( 2008); Trojanowski and Raizen (2016); Miyazaki, Liu and Hayashi ( 2017); others: Micchelli and Perrimon (2006), Ohlstein and Spradling (2006), Chaturvedi, Reichert, Gunage and VijayRaghavan ( 2017), Gunage, Dhanyasi, Reichert and VijayRaghavan (2017)…”
Section: Research Organisms For Agingmentioning
confidence: 99%
See 2 more Smart Citations
“…( 2016), Martino, Ma and Leulier ( 2017), Smith et al. ( 2017), Tropini, Earle, Huang and Sonnenburg ( 2017); excretory system: King and Goldstein (1985), Buechner (2002), Gautam, Verma and Tapadia ( 2017); sleep and circadian system: Raizen et al. ( 2008); Trojanowski and Raizen (2016); Miyazaki, Liu and Hayashi ( 2017); others: Micchelli and Perrimon (2006), Ohlstein and Spradling (2006), Chaturvedi, Reichert, Gunage and VijayRaghavan ( 2017), Gunage, Dhanyasi, Reichert and VijayRaghavan (2017)…”
Section: Research Organisms For Agingmentioning
confidence: 99%
“…A good example is the influence of gut microbiota on lifespan. A recent study using the turquoise killifish to address this question has revealed that not only the gut microbiota dynamically evolves with the host at different ages, but the host's lifespan can also be effectively extended by acquiring microbiota from the younger gut (Smith et al., 2017). The killifish short lifespan plays a key role to allow systematically characterize and manipulate the gut microbiota at different ages, and then assess their impact on the lifespan of the same individuals (Smith et al., 2017).…”
Section: Using the African Turquoise Killifish As A Research Organismmentioning
confidence: 99%
See 1 more Smart Citation
“…Transferring the microbiome of old mice to young germ-free mice led to upregulation of the proinflammatory cytokine tumor necrosis factor alpha (TNF-α), dysregulation of pathways involved in the immune response such as T cell differentiation and B cell development, and recognition of microbes by pattern recognition receptors. Additionally, levels of Akkermansia , TM7 bacteria, and Proteobacteria , all of which support inflammaging, were increased after microbiome transfer [16]. Even cohousing of germ-free with old mice resulted in an increased level of proinflammatory cytokines in the blood [18].…”
Section: The Role Of the Microbiome In Aging And Health Of Metaorganismsmentioning
confidence: 99%
“…In a microbiome transfer experiment from young fish to middle-aged individuals, a lifespan-extending effect was observed. Importantly, the fish also aged more healthily, which was observed by increased motility, a sign of being healthy [16]. …”
Section: The Role Of the Microbiome In Aging And Health Of Metaorganismsmentioning
confidence: 99%